Oliviculture and Viticulture Crop Byproducts Use for Peat Partial Substitution for Carnation Production - Antonios Chrysargyris; Panayiota Xylia; Nikolaos Tzortzakis (Agronomy, 2024)
The intensive cultivation of olive trees and grapevines in the Mediterranean region not only results in large yields but also generate wastes, with high restrictions on their impact on people’s well-being and the environment. The current study sought to investigate the potential use of olive-mill waste (OW), grape-mill waste (GW) and their mixtures (OW + GW) at different levels (0%, 5%, 10% and 20% v/v) for partial peat substitution in the production of carnation (Dianthus caryophyllus L.) plants. The presence of OW, GW and OW + GW wastes raised the pH, the electrical conductivity, the content of organic matter and mineral content in substrate mixtures, while they decreased the total porosity and the available free air. The use of OW had more negative impacts than GW, while the OW + GW mixture alleviated, to some extent, the negative OW impacts. The use of high levels of residues decreased plant growth, chlorophyll content and mineral accumulation in plant tissue due to inappropriate growing media properties. The increased OW presence caused oxidative stress to the plants, as verified by the increased malondialdehyde and hydrogen peroxide content. This resulted in an upsurge in the total phenolics. However, GW presence did not impact any oxidative stress. It can be suggested that 10% OW, 10% GW or 20% OW + GW can be used in growing media, as they resulted in suitable plant growth. To ensure sufficient yields, nevertheless, the growing media’s characteristics also need to be enhanced.